How is artificial lighting affecting the catches in deep water rose shrimp trawl fishery of the Central Mediterranean Sea?. (1st December 2021) - Geraci, Michele L.; Colloca, Francesco; Di Maio, Federico; Falsone, Fabio; Fiorentino, Fabio; Sardo, Giacomo; Scannella, Danilo; Gancitano, Vita; Vitale, Sergio
Abstract: The effect of artificial lights mounted on the headrope trawl net on the catch of deep water rose shrimp ( Parapenaeus longirostris ), European hake ( Merluccius merluccius ), and Atlantic horse mackerel ( Trachurus trachurus ) was tested in a survey carried out on-board a commercial trawler off the SW Sicilian coast. A total of 18 repeated nocturnal hauls, alternating without (control) and with (test) LED lights (10 green and 10 white) according to the fishers' setup, were conducted. Overall, the test net catch rates were not significantly higher than those of the control net (Kruskal-Wallis test, p > 0.05), except for P. longirostris (p < 0.05). Conversely, the two-tailed Kolmogorov–Smirnov test revealed statistical differences in the size structure of P. longirostris, M. merluccius, and T. trachurus between the test and control nets (p < 0.05). Using generalised linear mixed models, the test net was found to yield higher catches of undersized individuals of the three species and adults of P. longirostris than the control net. Our study results are discussed in the context of the exploitation and management of Mediterranean trawl fisheries. Graphical abstract: Image 1